Bridging the gap: A multi-level narrative review of leadership styles and knowledge hiding in organizations - Bilaludin Bilaludin; Indi Deli Fiallo Wibowo (Universitas Ahmad Dahlan, 2026)
Purpose-This narrative review examines how ten leadership styles, transformational, transactional, servant, ethical, abusive, altruistic, empowering, exploitative, humble, and self-serving shape employee knowledge hiding behavior in organizations, along with the mediating and moderating mechanisms that condition this relationship. Methodology-Through a thematic analysis of 26 empirical and conceptual articles indexed in Scopus and Web of Science, this study identifies two parallel pathways of influence. It synthesizes the conceptual mechanisms underlying each leadership–knowledge hiding relationship. Findings-A supportive-relational leadership style reduces knowledge hiding through psychological ownership, prosocial motivation, meaningful work, and positive affect. In contrast, a destructive leadership style increases knowledge hiding through perceived competition, employee silence, and emotional exhaustion. Notably, empowering leadership occupies an ambiguous, paradoxical position: it reduces knowledge hiding when employees possess adequate psychological resources, but exacerbates it under high hindrance stressors and high workload, depending on employees' resource conditions. Research Limitations-As a narrative review, this study did not systematically assess the methodological quality of individual articles. Most of the reviewed studies rely on cross-sectional designs, which limit causal inference, and the literature is dominated by East Asian and Western contexts, raising questions about the generalizability of the proposed framework to other cultural settings, such as Southeast Asia. Novelty-Building on social learning theory, social exchange theory, and conservation of resources theory, this study proposes a multi-level, multi-path conceptual framework. It demonstrates that the same mediating construct can produce opposing effects depending on the leadership context in which it operates, a finding that advances understanding beyond the single-style, single-mediator model.